Psychometric Properties of the Spanish Version of the Flow State Scale - García Calvo, Tomás; Jiménez Castuera, Ruth; Santos-rosa Ruano, Francisco Javier; Reina Vaíllo, Raúl; Cervelló Gimeno, Eduardo (The Spanish Journal of Psychology, 2008)
The purpose of this research was to examine the psychometric properties of a Spanish translation of the Flow State Scale (FSS; Jackson & Marsh, 1996). This instrument is used to assess the Flow State in participants of physical activity, although it can be adapted to other contexts (such as work, educational contexts, etc.). This construct can be considered the optimal psychological state to carry out an activity, being closely related to motivation and personal enjoyment (Csikszentmihalyi, 1997). A sample of 2036 athletes was recruited from diverse sports activities. The results revealed satisfactory validity and internal consistency of the instrument, obtaining a factor model made up of a main factor and nine subscales. The correlations between motivational orientations and the flow state are highlighted. The Spanish translation of this instrument is found to be acceptable, with similar psychometric properties as the original scale, although future research in other contexts is needed to support these outcomes.